IDENTIFICATION OF STUDENTS’ DIFFICULTIES IN MASTERING PASSIVE VOICE - Kadariyah, Nurlaila; Liani, Ida (English Department of Faculty of Tarbiyah and Teacher Training, 2013)
The research is conducted to find out of students? difficulties in mastering passive voice of the eleventh grade students at Islamic Senior High School Riadhusshalihi at Sinar Bulan cademic Year 2011/2012 The subject of the research is 35 students at the eleventh grade students of Islamic Senior High School Riadhusshalihin at Sinar Bulan academic year 2011/2012. The object of this research is identification of students? difficulties in mastering passive voice.The writer uses some techniques to collect data such as test, questionnaire, observation, interview and documentary. Data processing in this research is divided into five phases: editing, classification, scoring, tabulating and data interpretation. Then, all the data are analyzed by using descriptive qualitative and conclude by inductive method.The result of this research indicates that identification of students? difficulties in mastering passive voice of the eleventh grade Students at Islamic Senior High School Riadhusshalihin at Sinar Bulan Academic Year 2011/2012 is in fair category. The most of students? difficulty in mastering passive voice is identifying tenses whose 32 students or 91.43 % are wrong in answering the questions.